Sediment geochemical and geochronological analyses of OC170-26-159, Pacific-Antarctic Ridge - Lund, David; Asimow, Paul (IEDA: EarthChem Library, 2019)
Abstract: This dataset encompasses several different measurements on core OC170-26-159, including: 1) planktonic foraminiferal oxygen isotopes (0-230 kyr BP) and benthic oxygen isotopes (~120-150 kyr BP) measured on a Finnigan MAT 253 at the University of Michigan and Georgia Tech, 2) bulk elemental concentrations (0-230 kyr BP) measured on Thermo Element 2 at UCONN, 3) basaltic glass shard major elements (in two ash layers centered at ~140 kyr BP and 230 kyr BP) measured at Caltech using an electron microprobe, 4) trace element composition of the same shards determined using laser ablation ICP-MS at Caltech, 5) volatile content of the glass shards determined using FTIR at Caltech, and 6) shard grain size (for each ash layer) and settling velocity data for three separate size fractions of ash shards determined at UCONN. The full details of each method are described in the G-cubed related publication. Other Description: Lund, D. C., Seeley, E. I., Asimow, P. D., Lewis, M. J., McCart, S. E., & Mudahy, A. A. (2018). Anomalous Pacific-Antarctic ridge volcanism precedes Glacial Termination 2. Geochemistry, Geophysics, Geosystems, 19.